2014
DOI: 10.1371/journal.pone.0112882
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CD4+ T Cell Responses to Glutamic Acid Decarboxylase 65 Using DQ8 Tetramers Reveals a Pathogenic Role of GAD65 121–140 and GAD65 250–266 in T1D Development

Abstract: Susceptibility to type 1 diabetes (T1D) is strongly associated with MHC class II molecules, particularly HLA-DQ8 (DQ8: DQA1*03:01/DQB1*03:02). Monitoring T1D-specific T cell responses to DQ8-restricted epitopes may be key to understanding the immunopathology of the disease. In this study, we examined DQ8-restricted T cell responses to glutamic acid decarboxylase 65 (GAD65) using DQ8 tetramers. We demonstrated that GAD65121–140 and GAD65250–266 elicited responses from DQ8+ subjects. Circulating CD4+ T cells spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
(25 reference statements)
1
29
0
Order By: Relevance
“…To determine whether the epitopes recognized by these CD38+ T cells were presented by HLA-DR or HLA-DQ, we analyzed HLA restrictions for 10 oligoclones that we had cells available (Figure 4). We found that the reactivities of all these oligoclones were blocked by anti-HLA-DR antibody but not by anti-HLA-DQ antibody, including the reactivity to GADp32-specific peptide, which has been shown to contain a HLA-DQ restricted epitope [29] (Figure 4). These results suggest that all these oligoclones recognizes peptides presented on HLA-DR.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the epitopes recognized by these CD38+ T cells were presented by HLA-DR or HLA-DQ, we analyzed HLA restrictions for 10 oligoclones that we had cells available (Figure 4). We found that the reactivities of all these oligoclones were blocked by anti-HLA-DR antibody but not by anti-HLA-DQ antibody, including the reactivity to GADp32-specific peptide, which has been shown to contain a HLA-DQ restricted epitope [29] (Figure 4). These results suggest that all these oligoclones recognizes peptides presented on HLA-DR.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of antigen specific T cells in peripheral blood of T1D as well as HC subjects, even cells with a memory phenotype, has been a surprising finding (79, 51). The widespread detection of these islet antigen-reactive T cells may result from their expression of TCRs that cross react with pathogen derived antigens, as has been reported for the islet antigens insulin and IGRP (53, 54).…”
Section: Discussionmentioning
confidence: 99%
“…Several islet cell molecules were identified as targets of autoimmunity in T1D, including native proteins and epitopes of proinsulin (9,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63), GAD65 (64)(65)(66)(67)(68)(69)(70)(71)(72), tyrosine phosphatase-like insulinomaassociated antigen 2 (IA-2) (67, 73-75), islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP) (76-80), the cation + T cells, the predominant immune cell type in the insulitis. As described in the main text, these may include native antigens and neoepitopes.…”
Section: Loss Of Immunological Tolerance To β Cellsmentioning
confidence: 99%